Domestic violence and depression among married women: an example of Malatya - Gülpınar, Serdar; Güneş, Gülsen (Scientific Reports in Medicine, 2025)
Objective: This study aimed to determine the prevalence and types of domestic violence among married women in Malatya, Türkiye, examine associated sociodemographic and partner-related factors, and assess the relationship with depression. Method: A cross-sectional study was conducted with 398 married women aged 15–49 registered at a Family Health Center between January and April 2019. Data were collected through face-to-face interviews using a questionnaire including sociodemographic data, the Domestic Violence Scale, and the Beck Depression Inventory. As data distribution was not normal, non-parametric tests (including Kruskal-Wallis with Bonferroni post-hoc correction) and Spearman correlation were applied, with p<0.05 considered significant. Results: Most participants were ≥39 years old, unemployed/housewives, and had low education. Higher domestic violence scores were observed among younger, less-educated, and unemployed women, and those with younger, less educated, or unemployed spouses. Partner alcohol use, psychiatric illness, and history of violence were associated with increased violence. Probable depression was present in 13.3% and positively correlated with all violence types, especially verbal and total violence (r=0.433 and r=0.452, p<0.001). Conclusion: Domestic violence is common among young, less-educated, and socioeconomically disadvantaged women. Partner-related factors and exposure to multiple violence types increase depression risk. Findings support comprehensive prevention strategies addressing both visible and psychological violence and integrating routine mental health screening in primary care settings to facilitate early identification and intervention. This implies a clear recommendation for both clinical practice—proactive screening by healthcare providers—and public health policy aimed at protecting vulnerable women.